1990
DOI: 10.1192/bjp.157.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Altered Magnetic Resonance White-Matter T1 Values in Patients with Affective Disorder

Abstract: The MRI T1 proton relaxation values were assessedin 14 patients with bipolar affective disorder and 10 with a unipolar disorder and a matched normal control group. The T1values in the frontal white matter of patients significantlyexceeded those of the controls. This difference was accounted for by an increase in T1 values in the frontal white matter of unipolarpatients:the valuesfor bipolarpatientsalonedid not differ from those for controls. These preliminary findings support a hypothesis of frontal lobe dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…More recent in vivo imaging studies in patients with affective disorder have rendered mixed results. Some studies reported increased thalamic density (Dewan et al, 1988) and volume (Dupont et al, 1995;Strakowski et al, 1999) in bipolar patients, but other work has found that thalamic volume is either unchanged (Dolan et al, 1990;Krishnan et al, 1991Krishnan et al, , 1993Sax et al, 1999;Strakowski et al, 1993) or even decreased (Dasari et al, 1999;Dupont et al, 1995) in bipolar and unipolar depression.…”
Section: Glutamate Abnormalities and Thalamic Dysfunction In Affectivmentioning
confidence: 94%
“…More recent in vivo imaging studies in patients with affective disorder have rendered mixed results. Some studies reported increased thalamic density (Dewan et al, 1988) and volume (Dupont et al, 1995;Strakowski et al, 1999) in bipolar patients, but other work has found that thalamic volume is either unchanged (Dolan et al, 1990;Krishnan et al, 1991Krishnan et al, , 1993Sax et al, 1999;Strakowski et al, 1993) or even decreased (Dasari et al, 1999;Dupont et al, 1995) in bipolar and unipolar depression.…”
Section: Glutamate Abnormalities and Thalamic Dysfunction In Affectivmentioning
confidence: 94%
“…Studies have reported larger caudate volumes in males [105] and in both affected and unaffected monozygotic bipolar twins [106] compared to controls. However, other studies have found no differences in the caudate of bipolar disorder patients [107][108][109][110][111][112][113] or decreased caudate volume [114]. Similarly, putamen enlargement was reported [112,115,116], but other studies found no differences in the putamen [105,107,113] or decreased volume [117].…”
Section: Gray Matter Alterationsmentioning
confidence: 85%
“…Numerous other reports have also found greater total WML volumes in elderly depressed subjects (Krishnan et al, 1988;Dolan et al, 1990;Fujikawa et al, 1993;Krishnan, 1993;Greenwald et al, 1996;Steffens et al, 1999;Kumar et al, 2000;Tupler et al, 2002), but few of these studies examined the location of WMLs. Using an objective method of quantifying WML volume within each lobe, we have confirmed reports (Greenwald et al, 1998;MacFall et al, 2001;Taylor et al, 2003b;Firbank et al, 2004) that the preponderance of WMLs that are different between depressed and control populations occur in the frontal lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports associate hyperintense lesions with late-life depression. White and gray matter hyperintense lesions are more severe in older depressed subjects than nondepressed subjects (Krishnan et al, 1988;Dolan et al, 1990;Fujikawa et al, 1993;Krishnan, 1993;Greenwald et al, 1996;Steffens et al, 1999;Kumar et al, 2000;Tupler et al, 2002;Taylor et al, 2005), and are more severe in late-onset than early-onset elderly depressed subjects (Figiel et al, 1991;Hickie et al, 1995;Salloway et al, 1996;Krishnan et al, 1997;Lavretsky et al, 1998;de Groot et al, 2000;Tupler et al, 2002). Increases in WML severity over time are additionally associated with new onset of depression (Lavretsky et al, 1999;Nebes et al, 2002) and poorer outcomes to antidepressant therapy (Simpson et al, 1997;O'Brien et al, 1998;Taylor et al, 2003c), although some have not found a relationship between WML severity and treatment outcomes (Salloway et al, 2002).…”
Section: Introductionmentioning
confidence: 99%